2016
DOI: 10.24266/0738-2898-34.4.95
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Methanesulfonate and Caffeine Mutagenetic Treatment to Four Ornamental Silene Species

Abstract: Mutagenesis breeding for horticultural crops is valuable not only for creating new cultivars, but also expanding the genetic pool for hybridization. Four Silene species were subjected to ethyl methanesulfonate (EMS) and/or caffeine mutagenesis to obtain valuable ornamental traits and to test the effects of different mutagens and combinations. Species responded differently to the mutagens. Generally, caffeine plus EMS treatments had a greater effect on mutation rate than either treatment applied alone. Caffeine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…One of the breeding methods that can be applied to increase morphological diversity is artificial mutation. Mutation techniques have produced potential genotypes in various floricultural commodities [6,7]. One of the mutation sources that mutation breeders have widely used is ethyl methane sulphonate (EMS).…”
Section: Introductionmentioning
confidence: 99%
“…One of the breeding methods that can be applied to increase morphological diversity is artificial mutation. Mutation techniques have produced potential genotypes in various floricultural commodities [6,7]. One of the mutation sources that mutation breeders have widely used is ethyl methane sulphonate (EMS).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that using EMS could induce mutation in many ornamental plants such as rose [14], African violet [15], gerbera [16], Silene species [17], marigold [18] and chrysanthemum [19] also. Chrysanthemum is one of the most economically important cut flowers and ornamental plants across the global flower market.…”
Section: Introductionmentioning
confidence: 99%